The Correlation Between Time Management Skills and Students’ English Learning Outcomes - Wahyu, Wahyu; Dollah, Syarifuddin; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2025)
This research employs a quantitative approach aimed at examining the correlation between time management skills and students' English learning outcomes. The independent variable (X) in this research is time management skills, while the dependent variable (Y) refers to students' English learning outcomes. The research population consists of all grade XI students at SMA Negeri 2 Soppeng, with a sample of 49 students selected from various classes. Data collection was carried out using a questionnaire, which was distributed and completed online by the 49 participating students. Data analysis was performed utilizing SPSS 22 for Windows. The findings indicate that the time management skills (X) of grade XI students at SMA Negeri 2 Soppeng fall into the high or good category. Similarly, the average score of students' English learning outcomes (Y) is also categorized as high, with an average score of 88.67. Furthermore, the results reveal a significant correlation between time management skills (X) and students' English learning outcomes (Y), as evidenced by a significance value of 0.000 (< 0.05) and a correlation coefficient of 0.547. These findings suggest a moderately positive correlation between the two variables.